FUNCTIONAL FOOD COMPOSITIONS BASED ON WHEY PROTEIN ISOLATE, FISH OIL AND SOY PHOSPHOLIPIDS - D. V. Zelikina; M. D. Gureeva; S. A. Chebotarev; Yu. V. Samuseva; A. S. Antipova; E. I. Martirosova; M. G. Semenova (Пищевые системы)
The aim of the research was to study the impact of whey protein isolate on the solubility and oxidative stability of the lipid composition based on soy phosphatidylcholine and fish oil. The relationship between the molecular parameters (density; ζ-potential) of the formed complex particles and their functional properties was found using laser light scattering (static, dynamic, electrophoretic) and spectrophotometry. The studied compositions could be used as the basis for the development of multifunctional food additives with an objective of the enrichment of foods and beverages with omega-3 polyunsaturated fatty acids (PUFAs). The main advantages of such composition are a high level of protection of the lipids against oxidation and degradation, a high solubility in an aqueous medium and the clean label.